Information Technology Competencies of Educational Institution Administrators Under The Jurisdiction of Prachinburi Primary Educational Service Area Office 1 - Kaewkaraket, Jeerapa; Thongprong, Amnuay (Journal of Liberal Arts RMUTT, 2024)
This research aims to: 1) explore the information technology competencies of school administrators according to teachers’ perceptions within the jurisdiction of the Prachinburi Primary Education Area Office, Districts 1; and 2) compare teachers’ opinions regarding the IT competencies of school administrators within the jurisdiction of the Prachinburi Primary Education Area Office, District 1, categorized by educational qualifications, academic ranks, work experience, and school size. The sample group comprised teachers teaching in schools during the academic year 2566, with the sample size determined from the completed table of Cohen and colleagues, totaling 301 individuals, of which 276 responded, representing 91.69 percent. The research utilized a questionnaire with a 5-point Likert scale. The instrument’s index of congruence (IOC) was 1.00, and Cronbach’s alpha coefficient was .989. Statistical analyses included percentages, means (), standard deviations (S.D.), t-tests, one-way ANOVA, and paired sample t-tests. Findings revealed that: 1) overall, mean scores were high, with rankings from highest to lowest in the areas of knowledge and technology usage, leadership and vision, learning management support, technology promotion and management, and ethics, laws, and security. 2) Teachers with different educational qualifications had significantly different overall and specific opinions at the .05 level, with those holding higher qualifications expressing higher opinions than those with bachelor’s degrees. 3) Teachers with different academic ranks did not differ significantly in overall or specific opinions. 4) Teachers with different work experience levels significantly differed in overall and specific opinions at the .05 level, with those having more than 10 years of experience expressing higher opinions than those with less than 5 years. 5) Teachers teaching in schools of different sizes significantly differed in overall and specific opinions at the .05 level, with those teaching in large and medium-sized schools having higher mean scores than those teaching in small schools. The data from this study serve as guidelines for school administrators to enhance the quality, effectiveness, and management of education for future success and improvement.